On the role of distortion in the hcp vs fcc competition in rare-gas solids - Krainyukova, N.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
As a prototype of initial or intermediate structure somewhere in between the hcp and fcc lattices we consider a distorted bcc crystal. We calculate the temperature and pressure dependences of the lattice parameters for heavier rare gas solids Ar, Kr, Xe in the quasiharmonic approximation applying the Aziz potentials and confirm that in line with the previously found prevalence of hcp over fcc the hcp structure is still dominant in the bulk over the wide P–T ranges analyzed. The situation is different for confined clusters up to 105 atoms where owing to the specific surface energetics and terminations the structures with five-fold symmetry comprising fcc fragments are dominant. As a next step we consider a free relaxation of differently distorted bcc clusters, and show that two types (monoclinic and orthorhombic) of the initial distortion and its degree is a driving force for the hcp vs fcc final realizations. Possible energetic links between the initial and final structures are shown and analyzed.